ANTI-CULT ACCUSATIONS OF POLITICAL SUBVERSION AND SEXUAL ABUSE: TWO CASE STUDIES (Религиски дијалог и соработка, 2025)
This paper explores two facets of anti-cult criticism of groups labeled subversive or deviant in Chinaand the West. The methodology is based on an examination of available scholarly literature,media reports, and court decisions analyzed through theories of social control. The first case studyconcerns labeling as xie jiao and banning Qigong-based movements in China. The second discussesaccusations of sexual abuse targeting religious and esoteric groups in various Western countries.